Profile of scientific literacy competence student on temperature and heat matter - Y A Hidayat; P Siahaan; W Liliawati (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to obtain a scientific Literacy profile on a competency domain that refers to the PISA 2015 framework. Such competences include explaining scientific phenomena, interpreting data and scientific evidence, planning and evaluating investigations. The instrument used consists of 32 multiple choice. Based on the results of the analysis, the validity of the test used was 0.83 while the reliability is 0.76, both of which are high category. The research was conducted on the student class XII in one of the SMA Negeri in Bandung. The results show that the competence of student science literacy still low and need to be improved. Competence explains scientific phenomenon gets percentage 56, interpret and scientific proof gets percentage 58, while planning and evaluating experiment gets percentage 40.